Production of crude bio-oil via direct liquefaction of spent K-Cups. (December 2016) - Yang, Linxi; Mahmood, Nubla; Corscadden, Kenneth; Xu, Chunbao (Charles); He, Quan (Sophia)
Abstract: Spent K-Cups were liquefied into crude bio-oil in a water-ethanol co-solvent mixture and reaction conditions were optimized using response surface methodology (RSM) with a central composite design (CCD). The effects of three independent variables on the yield of crude bio-oil were examined, including the reaction temperature (varied from 255 °C to 350 °C), reaction time (varied from 0 min to 25 min) and solvent/feedstock mass ratio (varied from 2:1 to 12:1). The optimum reaction conditions identified were 276 °C, 3 min, and solvent/feedstock mass ratio of 11:1, giving a mass fraction yield of crude bio-oil of 60.0%. The overall carbon recovery at the optimum conditions was 93% in mass fraction. The effects of catalyst addition (NaOH and H2 SO4 ) on the yield of crude bio-oil were also investigated under the optimized reaction conditions. The results revealed that the presence of NaOH promoted the decomposition of feedstock and significantly enhanced the bio-oil production and liquefaction efficiency, whereas the addition of H2 SO4 resulted in a negative impact on the liquefaction process, decreasing the yield of crude bio-oil. Highlights: Spent K-cups as a new feedstock for liquefaction in ethanol-water mixture. Optimum conditions: 276 °C temperature, 3 min reaction time, 11:1 mass ratio of co-solvent and spent K-cups. The maximum crude bio-oil yield was 60% mass fraction and HHV of 25 MJ·kg − 1 . A promising option for disposing of spent K-Cups.